EKSISTENSI FIKIH DALAM PENERAPAN HUKUM ZINA DI INDONESIA - Ririn Isna Magfiroh; Az Zafi, Ashif (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
Criminal crime in Indonesia has become a challenge for the Indonesian people. In the application of law in Indonesia, it is still weak, because there are still many acts of adultery. The crime of adultery can cause moral damage to Indonesian children. The problem that is followed by adultery has won society and the nation so that it becomes a conflict that can disturb morale. Based on this background, the authors raise this article with the title The Existence of Fiqh in The Application of Adultery Law in Indonesia. Related to this scientific journal, the author explains the problem of applying zina laws in Indonesia, and the existence of fiqh in the application of adultery law in Indonesia. The research method used in scientific journals uses the literacy research method by analyzing books and journals that have the same discussion theme as the title of the article. What results of this renewal is that the application of adultery law in Indonesia is more effective, and firm. In order to avoid moral destruction of the younger generation. Because the young generation is the successor of the nation.